Changes in intra- and extramyocellular lipids in morbidly obese patients after non-surgical weight loss–a pilot study using magnetic resonance spectroscopy. (December 2018) - Fischer, Martin; Oberänder, Nadine; Kaufmann, Jörn; Kirsche, Viktor; Prodehl, Guido; Schäfer, Arnd-Oliver; Weimann, Arved
Summary: Background & aims: Lipid accumulation in muscles is common in obesity and associated with increased risks for insulin resistance. However, the impact of weight loss and exercise on muscle fat content is not clear due to inconsistent data. We used magnetic resonance spectroscopy (MRS) to compare the intra- (IMCL) and extramyocellular lipid (EMCL) proportions in the musculus tibialis anterior of extremely obese patients before and after weight loss. Methods: Nineteen non-diabetic patients with a Body Mass Index (BMI) ≥ 40 kg/m 2 who participated in a non-surgical multimodal weight loss program were recruited. Metabolite ratios of IMCL and EMCL (metabolite/creatine) were assessed using 3 T 1 H-MRS before therapy and after 6 months. The primary outcome comprised changes in IMCL and body cell mass. Additionally, changes of IMCL and EMCL were compared with changes in standard clinical measures, i.e., BMI, body composition, blood pressure and functional exercise capacity. Results: After 6 months the relative weight loss was 24.8% (127.6 kg, 48.5 kg/m 2 vs. 96 kg, 36.5 kg/m 2 ). All standard clinical measures were significantly improved. MRS data from 10 patients provided complete and evaluable data sets. IMCL was reduced by nearly 50% (p < .05). The reduction of EMCL was not significant (p = .106). An explorative correlation analysis between changes of IMCL and changes of the standard measures did not reveal any significance. Conclusions: Significant reductions of IMCL following a successful conservative weight loss intervention are detectable by using MRS. These changes may have the potential to serve as an additional marker of clinically meaningful obesity treatment.